1998
DOI: 10.1021/jp980235l
|View full text |Cite
|
Sign up to set email alerts
|

α,α-Trehalose−Water Solutions. II. Influence of Hydrogen Bond Connectivity on Transport Properties

Abstract: Results of photon correlation spectroscopy and viscosity measurements performed in trehalose aqueous solutions are reported. The light scattering experimental findings reveal a peculiar behavior of the effective diffusion coefficient D eff which, in the diluite region and in a limited temperature range, shows strong changes. This behavior suggests a great sensitivity of the system structure to temperature changes. On the other hand, the temperature dependence of shear viscosity η confirms the noticeable kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 17 publications
6
42
0
Order By: Relevance
“…84 The temperature dependent diffusion coefficient measurements of binary water− trehalose mixtures show that the activation energy for the diffusive motion falls in the typical hydrogen bond energy range. 85 We also observe that the translational dynamics of trehalose remains essentially unchanged for both the binary NT and ternary NUT systems. On the other hand, the diffusion coefficient of urea decreases from 1.15 × 10 −5 cm 2 s −1 in the binary NU system to 0.35 × 10 −5 cm 2 s −1 in the ternary NUT system.…”
Section: Resultsmentioning
confidence: 62%
“…84 The temperature dependent diffusion coefficient measurements of binary water− trehalose mixtures show that the activation energy for the diffusive motion falls in the typical hydrogen bond energy range. 85 We also observe that the translational dynamics of trehalose remains essentially unchanged for both the binary NT and ternary NUT systems. On the other hand, the diffusion coefficient of urea decreases from 1.15 × 10 −5 cm 2 s −1 in the binary NU system to 0.35 × 10 −5 cm 2 s −1 in the ternary NUT system.…”
Section: Resultsmentioning
confidence: 62%
“…Finally, it has also been suggested that the dependence of trehalose diffusion coefficient on concentration might reflect an aggregative process. 39,40 Trehalose self-association has further been demonstrated in ternary mixtures. The simulations of Lins et al have shown that trehalose at a moderate concentration of 0.5 M can cluster around the protein lysozyme, thereby trapping a thin layer of water molecules with modified solvation properties around the protein.…”
Section: Introductionmentioning
confidence: 96%
“…In this case, the particularly strong bioprotective capacity of TRH could be in large part a consequence of its very limited conformational flexibility in solution (low entropy cost of rigidification), secondary factors [19,20,81] being a favorable hydroxyl group disposition [82,83] (to interact with a planar surface), a strong propensity to self-aggregate [84,85], strong kosmotropic properties [86][87][88][89][90][91][92][93][94], an elevated glass transition temperature [81,95] (contribution of the VIH), a high chemical stability [81] (against acidic or enzymatic hydrolysis) and an antioxidant activity [96,97].…”
Section: Introductionmentioning
confidence: 99%